2017
DOI: 10.1002/rcm.7947
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for the methylation of aliphatic and aromatic compounds

Abstract: RationaleMethylation protocols commonly call for acidic, hot conditions that are known to promote organic 1 H/ 2 H exchange in aromatic and aliphatic C-H bonds. Here we tested two such commonly-used methods and compared a third that avoids these acidic conditions, to quantify isotope effects with each method and to directly determine acidic-exchange rates relevant to experimental conditions. MethodsWe compared acidic and non-acidic methylation approaches catalyzed by hydrochloric acid, acetyl chloride and EDCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The cores were split and stored at 4°C until analysis. Age models (Table S1) and analytical methods are described in the supporting information (Lee et al, 2017).…”
Section: Study Site: Lakes 327mentioning
confidence: 99%
“…The cores were split and stored at 4°C until analysis. Age models (Table S1) and analytical methods are described in the supporting information (Lee et al, 2017).…”
Section: Study Site: Lakes 327mentioning
confidence: 99%
“…We checked the linearity in isotopic determination across a range of peak amplitude (1 -10 V) daily, and only the measurements from compounds with peak amplitudes within the range of linearity were accepted. δ 13 C values were normalized to the Vienna Pee Dee (Lee et al, 2017) to report the δ 13 C and δD values of n-alkanoic acids.…”
Section: Compound-specific Isotopic Analysismentioning
confidence: 99%
“…FAME fractions were then taken to dryness in a stream of N2. The isotopic value of the methanol was determined through methylation of a phthalic acid with known isotopic value (Lee et al, 2017).…”
Section: Biomarker Distributions and Stable Carbon Isotope Analysismentioning
confidence: 99%
“…Reference material F8-3 was also used to determine the usable amplifier signal range, which minimized the residuals, and (ranging from 0.21 to 0.34‰, n=21). Fatty acid  13 C was calculated through mass balance corrections of the measured FAME  13 C and known  13 C of the added methyl group (Lee et al, 2017) and reported relative to Vienna PeeDee Belemnite (V-PDB).…”
Section: Biomarker Distributions and Stable Carbon Isotope Analysismentioning
confidence: 99%